(untitled) (Eurasian Scientific Herald, 2022)
In this article, there exist information about Uzbek wrestling that educating the young to be courageous, brave, modest, honest, loyal and ready to defend their home country with no fear and hesitation in PE classes has been set as the main goal in it.